Myocardial stunning after streptokinase: what is the significance of the Q wave?. Issue 6 (1st June 2000) - Keeble, W; Martin, W; Hutton, I
Abstract : A 58 year old woman presented with symptoms and electrocardiographic features consistent with acute infero-posterior myocardial infarction. The attempt at reperfusion with aspirin and thrombolytic treatment was deemed unsuccessful in view of Q wave development on ECG, a 48 hour period of hypotension and oliguria, and extensive wall motion abnormality on echocardiography. This was at variance with findings of a minimal cardiac enzyme rise. On the seventh day, list mode acquired, ECG gated, cineimages of perfusion and blood pool demonstrated strikingly normal perfusion despite continued contractile dysfunction. Six weeks later ECG, echocardiography, and radionuclide blood pool ventriculography had all normalised consistent with resolution of myocardial stunning. This practical method for the diagnosis of stunning, the significance of the ECG changes in particular the development of Q waves, and the time taken to resolution of this phenomenon are discussed.